Can we talk about good professional dialogue?. (2nd January 2021) - Harris, Sean
Abstract : Schools within the Consilium Academies MAT are using professional development discussions to secure school improvement, boost teacher development and ensure that teachers have the opportunity to talk. Sean Harris finds out more